IDENTIFYING THE DIMENSIONS OF SERVICE QUALITY AS ANTECEDENTS TO PASSENGER SATISFACTION OF RAJIV GANDHI INTERNATIONAL AIRPORT (A RESEARCH PAPER) - Raja, Archana (Journal of Contemporary Research in Management (JCRM), 2013)
This paper explores on service quality of an International airport of Hyderabad, which is more influenced on the passenger satisfaction. Measuring and improving service quality has become an important task for many of the airline companies. Previous researchers have contributed much on SERVQUAL and SERVPREF which is been applied in many of the marketing studies that deals with the customer satisfaction. Based on the sound contribution of the researchers, a 20 – item scale was developed for this study. Through factor analysis a five dimension service quality study has been obtained. The result from the analysis has suggested that all the five dimensions of service quality as well as service range influences the passenger satisfaction. The information endowed with the study can be used for designing the marketing strategies to improve the passenger satisfaction in aviation industry.